Trends in developments in gas-shielded arc welding equipment in Japan - Tomoyuki Ueyama (Автоматическая сварка, 2013)
In the welding field in Japan, new technologies and processes have been developed one after another in response to the
improvement in materials and the changes in the market needs, which have remarkably been contributing to rationalization
and cost reduction in various industries. Taking into account the abovementioned technological trends, this paper provides
an overview of the present situation of technological developments in terms of gas shielded arc welding equipment.